B cells from old mice induce the generation of inflammatory T cells through metabolic pathways. (January 2023) - Li, Kevin; Romero, Maria; Cañardo, Macarena; Garcia, Denisse; Diaz, Alain; Blomberg, Bonnie B.; Frasca, Daniela
Abstract: We have measured the capacity of B cells from young and old mice to induce the differentiation of naïve CD4 + T cells from young mice into pro-inflammatory subsets. We found that only B cells from old mice are inflammatory and induce in vitro secretion of the pro-inflammatory cytokines IL-17A and IFN-γ by T cells. In co-culture experiments, B cells from old mice showed a strong helper function on T cells from young mice, making them pro-inflammatory, and this effect is regulated by metabolic pathways, mainly anaerobic glycolysis, leading to increased RNA expression of the enzyme lactate dehydrogenase (LDHA) and increased secretion of lactate. These results have indicated that lactate is a crucial player of the B cell-induced polarization of T cells. When we measured the effects of lactate on isolated CD4 + T cells from young mice, we found that lactate increases RNA expression of LDHA, secretion of pro-inflammatory cytokines and NF-kB activation. Moreover, lactate effects in culture can be abrogated in the presence of the specific inhibitor of LDHA, FX11. These results altogether may have relevant clinical implications and suggest novel targets for therapeutic interventions in patients with inflammatory conditions and diseases. Highlights: B cells from old but not from young mice are inflammatory. B cells from old mice polarize CD4 + T cells from young mice to become inflammatory. B cells polarize CD4 + T cells through metabolic pathways (glycolysis). Lactate is at least one metabolic mediator of B cell-induced CD4 + T cell polarization.